Unusual Excessive Swelling of the Tongue after Calcium Acetate Ingestion: A Case Report - TAŞLIDERE, BAHADIR; Dal A.; Taslidere B. (My University, 2023)
Common side effects of calcium acetate include increased blood calcium levels, nausea-vomiting, diarrhea, and fatigue, while side effects of unknown incidence include \"swelling\". We present the case of an allergic reaction limited to tongue swelling alone, not showing other anaphylactic symptoms. Our case was a female patient who applied to the emergency department with the complaint of isolated tongue swelling three hours after using calcium acetate for treatment. It should be kept in mind that calcium acetate, a food additive, may cause this in patients with the complaint of isolated tongue swelling, but the cause of which cannot be determined.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE